Analysis about the Experiences and Perceptions expressed by Foreigners regarding the Kinesics Employed in Bogotá. (2017)
The aim of the present research evidences the importance that non-verbal communicative acts have on the daily life interactions, particularly in other cultures with no a tight relation or an evident disparity. For this reason, this is a qualitative research study, based on this assumption some foreigners were interviewed to expose their knowledge about the kinesic communication or body language, focusing this communicative kind in our context. In this mode, this research seeks to inspect about the way how gestures could influence in communicative interactions among foreigners who visit or live in a region which has a different culture and costumes. With the purpose of spreading the knowledge about the perception that the participants of this work can express about the perceptions about the influence of gestures in the understanding and emission of messages during any kind of communicative interaction. Thanks to the information collected through these interviews is possible to know more about possible scenarios, if anyone faces different cultural representations of communication in an immersion context. This study also pretends to seek convergence points while participants experience this communicative type in order to allow the readers to take references of what is stipulated in this study. Furthermore, the information gather in this study can help the readers to enhance their knowledge concerning the exchange of kinesic influences from one culture to another.